Investigation the Association of the VEGFR-2 and -2578CPolymorphism as a Risk Factor for Incidence of Lung Cancer in Babylon Province - Ali K. Dahir1 , Alaa S. Al-Awad2 , Moaed E. Al-Gazally3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: VEGF gene polymorphisms can induce either increase or inhibition of VEGF secretion, with altered promoter activity. Aim: We investigated the association of the VEGFR-2 and -2578Cpolymorphism in the VEGF gene with Lung cancer risk in Babylon province. Methodology: VEGFR-2 level was measured by Enzyme Linked Immunoabsorbant Assay ELISA and Genotyping of the VEGF-gene variation (-2578A) was performed using the amplification refractory mutation system PCR. We investigated the association of VEGF gene variants with different clinicopathological features of lung cancer patients. Results: No significant difference was seen of the VEGFR-2 levels in lung cancer patients when compared with control group (P=092), the allelic frequency of -2578 AVEGF gene no difference was seen in patients lung cancer (p=0.652). Hardy-Weinberg equilibrium showed a significant difference cases group (p=0.016), also revealed A allele exhibits a pathological behavior and it appears in over-dominant model (p=0.05), this proves that there is significant association of -2578AVEGF gene in lung cancer patients. Conclusion: Our results showed no significant association of the VEGFR-2 in lung cancer patients while showed a significant association of the VEGF -2578Cpolymorphism with LC susceptibility in Babylon province .The VEGF -2578Cheterozygote significantly increases the risk and can be useful as a predisposing genetic marker.